Captação e tratamento de águas residuárias em tempo seco : revisão integrativa de literatura e contribuições para discussões sobre aspectos técnicos, econômicos, ambientais, sociais, legais e institucionais - Felipe José Vorcaro de Toledo (2023)
The panorama of sewage services in Brazil indicated in 2017 that 43% of the population was served by the collective system, comprising the collection network and sewage treatment plant; 12% were assisted by individual solution, with septic tank; 18% had collected but untreated sewage; and 27% of the population did not receive any assistance, that is, without sewage collection or treatment. Just over half (55%) of the population received adequate sewage services, less than half of Brazilian municipalities (46%) had separate sewage systems and a small portion (14.7%) had combined systems. Although the separate system is the most used, in practice they do not operate as designed and dysfunctionalities resulting from misconnections between sanitary and storm sewers are frequent, which compromises the efficiency of the systems, public health and environmental balance. This panorama drives to alternative planning approaches for sanitary sewage systems; and, in this context, the dry weather sewage intake and treatment (DWSIT) of wastewater that run through urban storm water system have been discussed and adopted in Brazil in recent years as a complementary alternative to the hegemonic concepts of engineering based exclusively on separate systems. The DWSIT aims to promote more effective control of pollution in the short term during non-storm periods, directing sewage for treatment. Therefore, the research critically analyses, based on an integrative literature review, the concepts and practices of DWSIT related to different aspects: technical; economical; environmental; social; institutional; and legal, considering the Brazilian scenario. In the integrative review, 2391 publications were identified in databases (English and Portuguese) by reading the titles and abstracts; included 25 publications related to the topic to be fully read; additionally there were selected another 36 publications by reading their references; a total of 61 publications were included for reading and analysis. Of these 61 publications, 15 are focused on DWSIT systems and 17 only mention them, without detailed discussion. The DWSIT still lacks operation and tariff regulation in Brazil and the spread of the technique has been identified in recent years, which will be increased due to the approval of Federal Law No. 14.026 of 2020. In addition, there are relatively few academic studies on the subject, which indicates the need for technical advances for its use, even more considering the actual understanding that combined systems are accepted in periods of transition to the ideal separate sewer system. The use of DWSIT occurs in other countries, especially in China, where they have been implemented for decades and there is an obligation for their use in some cities. DWSIT systems can bring benefits that are already identified in places where they are implemented and further advances are needed from the point of view of national technical standards and the evaluation of economic, environmental and social aspects in the Brazilian context so that planning and operation can achieve the best results.